2014
DOI: 10.1038/eye.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal retinal imaging in a Chinese kindred with familial amyloid polyneuropathy secondary to transthyretin Ile107Met mutation

Abstract: Objective To investigate the ocular phenotype and gene mutation of a Chinese pedigree with familial amyloid polyneuropathy (FAP) and vitreous amyloidosis. Methods A Chinese pedigree with familial amyloid polyneuropathy and vitreous amyloidosis was recruited. Combined phacoemulsification, vitrectomy and intraocular lens implantation were performed on the right eye of the index patient. Ophthalmic investigations were performed before and after surgery. The DNA from the pedigree was sequenced for the transthyreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The standard ophthalmological examination including dilated fundus examination with a 90D lens can detect most of the vascular changes associated with ATTRv. The main vascular clinical findings described in ATTRv patients were: tortuous retinal vessels 7 , 11–13 microaneurysms 10 , 12 retinal hemorrhages 5 , 7 , 10 , 14–18 sheathing of retinal vessels 7 , 14 , 17 , 18 whitish amyloid deposits along retinal arteries 7 , 12 , 15 , 19–21 obliteration of retinal vessels 5 , 7 , 15 , 20 pre-retinal neovascularization 10 vitreous hemorrhage 18 , 22 iris neovascularization 10 , 22 (anterior segment biomicroscopy). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard ophthalmological examination including dilated fundus examination with a 90D lens can detect most of the vascular changes associated with ATTRv. The main vascular clinical findings described in ATTRv patients were: tortuous retinal vessels 7 , 11–13 microaneurysms 10 , 12 retinal hemorrhages 5 , 7 , 10 , 14–18 sheathing of retinal vessels 7 , 14 , 17 , 18 whitish amyloid deposits along retinal arteries 7 , 12 , 15 , 19–21 obliteration of retinal vessels 5 , 7 , 15 , 20 pre-retinal neovascularization 10 vitreous hemorrhage 18 , 22 iris neovascularization 10 , 22 (anterior segment biomicroscopy). …”
Section: Resultsmentioning
confidence: 99%
“…One study reported better visualization of amyloid deposits along the vessels with red-free confocal retinography, versus conventional retinography. 19 Ultra-widefield retinography may be useful to detect and document peripheral lesions. 7 …”
Section: Resultsmentioning
confidence: 99%
“…However, TTR‐FAP is now believed to have worldwide distribution (Benson and Kincaid, ) . More and more TTR‐FAP patients in Han Chinese people have been reported (Table ) (Yamamoto et al , ; Chou et al , ; Lachmann et al , ; Li et al , , ; Lim et al , ; Mak et al , , ; Liu et al , , , ; Yang et al , ; Chen et al , ; Zhang et al , , ; Long et al , ; Zou et al , ; Lv et al , ; Meng et al , ) . Here, we identified four different TTR heterozygous mutations already known to be associated with FAP in four unrelated families and among them, mutations Thr49Ala(p.Thr69Ala) and Tyr116Ser(p.Tyr136Ser) were detected for the first time in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, TTR Ala97Ser is the most common mutation 9,10 . However, a limited number of cases of ATTR have been reported in the form of case reports in mainland China 11–50 . The clinical and genetic profiles of ATTR in mainland China remain elusive.…”
Section: Introductionmentioning
confidence: 99%